EJEL Editorial 2024: The Allure of AI in Education - Paula Charbonneau-Gowdy; Marija Cubric; Ronald Dyer; Alessandro Pagano; Katya Pechenkina; Heinrich Söbke; Pia Spangenberger (Electronic Journal of e-Learning, 2024)
The objectives of this editorial are to provide a brief overview of the themes of EJEL papers published in 2023, compare these themes with the areas of work suggested in the previous Editorial (Charbonneau-Gowdy, et al., 2023), and propose new areas of focus for future research. The present Editorial will primarily concentrate on the main challenges arising from the release and use of GPT-3 and GPT-4 in 2023.